Advances in culture and psychology. Volume 1 - Gelfand, Michele J.; Chiu, Chi-yue, 1963-; Hong, Ying-yi, 1964- (New York ; Oxford : Oxford University Press, 2011)
With applications throughout the social sciences, culture and psychology is a rapidly growing field that has experienced a boom in publication over the last decade. Comprising chapters from internationally renowned culture scholars, this book represents diversity in the theory and study of culture within psychology.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 12, 2011).
Keywords: Ethnopsychology; Culture